Ecophilosophy, Praxis, and the Deconstruction ofAnthropocentrism in Richard Powers the Overstory (Journal of Asian Development Studies, 2024)
This paper analyses the relationship among eco-philosophy, praxis, and the deconstruction ofanthropocentrism in Powers' (2019) The Overstory, utilizing the theoretical framework ofDeep Ecology as advanced by Arne Naess (1989). Powers' work challenges the prevailinganthropocentric perspective, presenting an eco-realm in which trees and ecosystems serve asprimary protagonists, questioning the hierarchical distinction between humans and nature.This study, informed by Naess's concepts of Deep Ecology, such as intrinsic value, ecologicalself-realization, and biocentric equality, examines how The Overstory (2019) promotes atransition from anthropocentric ethics to a life-centered environmental ethos. The studyexamines the praxis derived from Power's narrative, highlighting the novel's advocacy forenvironmental action, shared responsibility, and a redefinition of humanity's position withinthe biosphere. It emphasizes the metamorphic capacity of the story in cultivating ecologicalawareness, suggesting that the novel acts as a medium for reevaluating, redefining ecologicalethics, and prompting action against environmental degradation. This study argues that byintegrating Naess's (1989) theoretical framework with literary analysis, the novel challengesanthropocentrism while proposing a realistic approach to biocentric life, encouraging readersto adopt ecological interdependence and activism. Integrating the ecophilosophy of deepecology and practice highlights the novel's importance in contemporary environmentaldiscourse.